2021
DOI: 10.1097/ftd.0000000000000846
|View full text |Cite
|
Sign up to set email alerts
|

An Ultrafast Ultrahigh-Performance Liquid Chromatography Coupled With Tandem Mass Spectrometry Method for Cannabidiol Monitoring in Pediatric Refractory Epilepsy

Abstract: Background: Cannabidiol (CBD) is a nonpsychoactive natural product that has been increasingly used as a promising new drug for the management of neurological conditions such as refractory epilepsy. Development of rapid and sensitive methods to quantitate CBD is essential to evaluate its pharmacokinetics in humans, particularly in children. The objective of this work was to develop and validate an ultrafast ultrahigh-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…Several assays for determining CBD in different biological matrices such as peripheral capillary blood, plasma, serum, saliva, urine, breast milk and hair have been reported recently ( Pérez Montilla et al, 2021 ; Sempio et al, 2021b ; Cliburn et al, 2021 ; da Silva et al, 2020 ; Desrosiers et al, 2015 ; Cobo-Golpe et al, 2021 ; Reber et al, 2021 ). Although a few of these assays have also been validated for measuring the active metabolite 7-hydroxy-CBD in plasma or serum samples ( Sempio et al, 2021a ; Malaca et al, 2021 ), to our knowledge the present HPLC-MS/MS method is the first reported assay that permits the simultaneous determination of CBD and its active metabolite 7-hydroxy-CBD in both human serum and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Several assays for determining CBD in different biological matrices such as peripheral capillary blood, plasma, serum, saliva, urine, breast milk and hair have been reported recently ( Pérez Montilla et al, 2021 ; Sempio et al, 2021b ; Cliburn et al, 2021 ; da Silva et al, 2020 ; Desrosiers et al, 2015 ; Cobo-Golpe et al, 2021 ; Reber et al, 2021 ). Although a few of these assays have also been validated for measuring the active metabolite 7-hydroxy-CBD in plasma or serum samples ( Sempio et al, 2021a ; Malaca et al, 2021 ), to our knowledge the present HPLC-MS/MS method is the first reported assay that permits the simultaneous determination of CBD and its active metabolite 7-hydroxy-CBD in both human serum and saliva.…”
Section: Discussionmentioning
confidence: 99%
“…y publicaciones de investigaciones (siempre asociadas a temas de farmacocinética y farmacología clínica, aunque no solo de antibióticos), observamos un incremento sostenido a lo largo del período evaluado (cantidad media de presentaciones por año, por período: 4 en 2007-2010 vs 7 en 2011-2020). En este sentido, el cambio más relevante se produjo en relación a la importancia, medida en términos del factor de impacto de las revistas en la que fueron publicados estos trabajos, correspondiendo los de la última etapa a revistas de mayor factor de impacto en relación al primer período (26)(27)(28)(29) . Asimismo, las actividades de formación de recursos humanos en ámbitos profesionales, incluyendo a universidades, sociedades científicas y demás instituciones de similar envergadura, también mostraron un incremento constante (cantidad media de actividades docentes por año, por período: 5 en 2007-2010 vs 11 en 2011-2020).…”
Section: Discussionunclassified
“…Quantification of CBD was performed by means of a validated method using ultrahigh-performance liquid chromatography coupled with tandem mass spectrometry (UHPLC-MS/MS) as previously reported. The assay was linear in the range of 1–300 ng/mL, the lower limit of quantification for CBD was 0.9 ng/mL, and intra-day precision was >96% [ 21 ].…”
Section: Methodsmentioning
confidence: 99%